EFFECT OF INTERNAL CONTROL EFFECTIVENESS, COMPENSATION SYSTEM, INFORMATION ASYMMETRY AND ACCOUNTING RULES, ACCOUNTING MORALITY TO JENDING ACCOUNTING TENDENCY OF ACCOUNTING SHORT BEHAVIOR WITH ENTERVENING VARIABLES (Empirical Study at Adventist Schools in - Erwinto Simbolon; Adji Suratman Hendri (Program Studi Magister Manajemen Universitas Advent Indonesia, 2020)
The purpose of this research to study the effect of the effectiveness of internal control, compensation systems, information asymmetry and compliance with accounting rules with unethical behavior towards fraudulent accounting trends. This study is to examine the extent to which the influence of the effectiveness of internal control and unethical behavior on accounting fraud tendencies. This research was conducted on the population of Adventist Schools in Jakarta with Random Sampling in 15 schools and 5 respondents from each sample. The method used by the Structural Equation Model (SEM) approach uses Partial Least Square (PLS) software. The results of the study show: there is a significant and positive influence; The effectiveness of internal control on unethical behavior, the effectiveness of internal control on Accounting Fraud Trends, Compensation System for Unethical Behavior, Compensation System for Accounting Fraud Trends, Information Asymmetry for Unethical Behavior, Compliance with Accounting Rules for Unethical Behavior, Management Morality against Behavior is not Ethical, Management Morality towards Accounting Fraud Trends, Unethical Behavior towards Accounting Fraud Trends, but Information Asymmetry on Accounting Fraud Trends, and Obedience of Accounting Rules to Accounting Fraud Trends has a positive but insignificant effect From the results of these studies, the authors make all positive influences. However, there are two insignificant hypotheses, namely the influence of information asymmetry on accounting fraud and compliance with accounting rules for accounting fraud tendencies. And the relationship between variables is very good for improving internal control in preventing accounting fraud tendencies.